Nano-biosensors in cellular and molecular biology - Moradi, Sajad; Khaledian, Salar; Abdoli, Mohadese; Shahlaei, Mohsen; Kahrizi, Danial (Cellular and Molecular Biology, 2018)
Detection and quantification of various biological and non-biological species today is one of the most important pillars of all experimental sciences, especially sciences related to human health. This may apply to a chemical in the factory wastewater or to identify a cancer cell in a person's body, it may be apply to trace a useful industrial microorganism or human or plant pathogenic microorganisms. In this regard, scientists from various sciences have always striven to design and provide tools and techniques for identifying and quantifying as accurately as possible to trace various analyte types with greater precision and specificity. Nano science, which has flourished in recent years and is nowadays widely used in all fields of science, also has a unique place in the design and manufacture of sensors and this, in addition to the new and special characteristics of nanoparticles, is due to the ability of nano-devices to penetrate into very tiny places to track the species. On the other hand, due to the high specificity of biological molecules in identifying and connecting to their receptors that have evolved over millions of years, Scientists are now trying to design hybrid devices using nano science and biology, called Nano-biosensors So that they can trace and quantify target molecules in very small amounts and in inaccessible places, such as within the organs and even the cells.